Kajian Penggunaan Antibiotik Pada Peternakan Babi Di Kecamatan Kota Raja Kota Kupang - Debora Irene Weki; Maxs U.E Sanam; Tri Utami (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
The main cause of antibiotic resistance is the use of antibiotics that are misuse and overuse. Another factor is the misunderstanding of the use of antibiotics, the incorrect dosage of antibiotics, the many uses of broad-spectrum antibiotics and antibiotics that are sold freely without a doctor's prescription. This study aims to determine the percentage of antibiotic use among pig farms and the types of antibiotics used by pig breeders in the treatment of pigs in District of Kota Raja, Kupang City. A total of 80 respondents spread across eight sub-districts in District of Kota Raja, Kupang City. Information regarding the use of antibiotics was obtained through observation and structured interviews in the form of questionnaires distributed to pig farmers. Data were analyzed descriptively and then displayed in tables and figures. The percentage of pig farmers who use antibiotics in Kota Raja Subdistrict, Kupang City reaches 81.03% (47 farmers). The types of antibiotics used by pig breeders in District of Kota Raja, Kupang City are Oxytetracycline (57.45%); Sulfadimidine and Amoxicillin (6.38%) ; Procain Penicillin G and Dyhidrostreptomycine sulpphate (2.13%); Sulfadiazin sodium, Sulfadimine sodium and Sulfamerazinesodium (4.26%); and there was use of other types of antibiotics (23.4%) that were not identified by the farmer.